Health tourism in Lviv region: current state and development prospects - Kovalchuk, Iryna; Kovalchuk, Andrii; Zapototskyi, Sergii; Zapototska, Victoriia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Introduction. Health tourism is considered a kind of tourism which is carried out for the purpose of prevention of various diseases and the recreation and provides for guests accommodation in sanatorium-and-spa establishments. This is a special form of tourism, which includes providing medical treatment (often non-drug) or health improvement services. Problem formulation. Health tourism takes one of the leading places in the tourism industry. This is mostly caused by the increase in the population wellbeing. Analysis of recent research and publications. Studies of the development of health tourism in general and in the Lviv region in particular are presented in the works of many Ukrainian and foreign scientists. The article fulfilled the analysis of foreign and domestic sources, which allowed to identify the following ideas that are of interest for the study of health tourism in Lviv region and many other regions of Ukraine Highlighting previously unsolved parts of the overall problem. The fulfilled study allowed us to assess approaches to the analysis of the current state of health tourism in general and in the Lviv region in particular. The literature is dominated by the opinion that the resort sphere of Lviv region attracts tourists with both favorable prices and a wide range of available services. The issues of estimating the tourist flows coming into the territory of Lviv region were also considered. At the same time, insufficient attention was paid to the study of the status of medical tourism, to the substantiation of proposals aimed at optimizing the development and the improvement of functioning of spa resorts in Lviv region. Formulating the purpose of the paper. The focus of this paper will be set on an objective assessment of the current conditions of the tourism industry based on a quantitative analysis of available statistical data with cartographic and modern statistical methods. Presentation of the main research material. The main directions of formation and development of health tourism in the world are outlined. Cheap health care and leisure services are provided mainly in the resorts of Asia, Latin America and Australia, as well as in some European countries. This is due to the cost of labor, as well as global pricing mechanisms. The main stages in the development of health tourism in Lviv region are distinguished. The description of Lviv region as an arena for the development of health tourism is given. Spa resorts of Lviv region are attractive first of all by the prices, and also by the wide range of available services. The resort sphere of Lviv region has been studied. Tourist flows in the region are being characterized. Conclusions. The main means of popularizing spa resorts of Lviv region have been identified, including advertising, Internet sources, exhibitions, forums and conferences. The proposals have been worked out directed on optimization of development and improvement of functioning of spa resorts of the Lviv region.